Halala: An Exceptional Marriage Practice in Islam - Ojha, Niranjan (Journal of Development Review, 2021)
The study of a religious minority like Muslims keeps greater importance in the country like Nepal where the majority population is Hindu. Marriage, divorce are the common phenomenon of the society. Remarriage after divorce is also common in Nepali society but remarriage with same bride after divorce in Muslim community is exceptional and the process is very curious to Nepali society. This paper tries to discuss the exceptional marriage practice in Islam i.e. Halala marriage. Marriage is a contract between bride and groom for the purposes of the legislation of intercourse, procreation of children and the social contract between husband and wife. Muslims practices marriage ritual according to the Muhammadan law. According to Holy Quran, if a husband divorces his wife, he is not allowed to remarry her until she has married to another husband and he has divorced her. Halala marriage is a practice in the Muslim community which allows a man to re-marry his wife after Triple-Talaq. Halala has been severely criticized as it harms the dignity of a woman by forcing her into a compromised sexual relationship. This research attempts to deal with the overall scenario of Nikah Halala.